On Cosmopolitan Distribution of Pista cristata (Polychaeta, Terebellidae). - Saphronova, M. A. (Zoologicheskii zhurnal, 1988)
Cosmopolitan species Pista cristata (Muller, 1776) has been partially revised. Data are reported on the taxonomic characters used to divide and describe the new species. Four species are described, previously identified by different authors as P. cristata, among them - P. bansei sp. ?., P. wui sp. n. and P. paracristata sp. n. Scionella lomensis Pearson, 1969 has been transferred into the genus Pista. P. bansei sp. n. has one pair of gills and is most closely related to P. lomensis, from which it differs by its upper lip, the size of the lateral lappets of the 3d segment and by the shaft of thoracic uncini in adults. P. bansei sp. n. is characterized by age modification of the length of the shaft of uncini. P. wui sp. n. differs from P. lomensis and P. bansei sp. n. by two pairs of gills, size ratio of lateral lappets of the first segmenti, by the shaft of thoracic uncini in adults and juveniles. P. paracristata sp. n. differs from the most close species P. wui sp. n. by the shape of the upper lip, size of the lateral lappets of the 4th segment and their shape, stronger chitinization of the shaft of uncini.
World Polychaeta Database (WPolyD).